Impact on Employee Satisfaction, Brand Commitment and Employee Turnover- Role of Employer Branding - Syal, Ginni (The journal of contemporary issues in business and government, 2021)
The results of the study have indicated that in order to secure the lifelong success of any banking institution the retention of key bank employees have been critical factor to be taken into consideration. It has been observed that it is more profitable for organizations to have good and attractive brand name, which reflects employees’ perception of employer and their beliefs and values about the bank. By providing employees with social security, economic stability and career development, they will be more satisfied, more committed towards keeping the brand name and are less likely to leave for another banks. Therefore, it becomes necessary for the bank employers to keep their employees happy and contended in the bank culture by providing them an attractive work environment